IL-6 and PD-L1 blockade combination inhibits hepatocellular carcinoma cancer development in mouse model - Liu, Hu; Shen, Jun; Lu, Kai (Biochemical and biophysical research communications, 2017)
Limited efficacy of immune checkpoint inhibitors in hepatocellular carcinoma (HCC) was observed in clinical trials, thus prompting investigation into combination therapy. Interleukin-6 (IL-6) has important roles in modeling immune responses in cancers. Here, we hypothesized that IL-6 blockade would enhance antitumor immunity of HCC and synergize with anti-programmed death-1-ligand 1 (PD-L1) checkpoint inhibitor in treating HCC. The sources and immune modulating effects of IL-6 were investigated in HCC models. Combination of anti-IL-6 and anti-PD-L1 was tested in HCC bearing mice. We found that IL-6 is mainly secreted by cancer associated fibroblast (CAFs), but not tumor cells in HCC. High IL-6 expression CAFs could induce strong immunosuppression in HCC microenvironment by recruiting immunosuppressive cells, such as myeloid derived suppressive cells. In addition, high IL-6 expression CAFs also impaired tumor infiltrating T-cell function via upregulating inhibitory immune checkpoints. Using IL-6 blockade could reverse anti-PD-L1 resistance in HCC tumor model. In conclusion, our study indicates that targeted inhibition of IL-6 may enhance the efficacy of anti-PD-L1 in HCC, providing a potential strategy to overcoming anti-PD-L1 resistance in HCC. •IL-6 was highly expressed in CAFs but not HCC tumor cells.•IL-6 expressed by CAFs promoted the development of HCC in mouse model.•IL-6 expressed by CAFs promoted the recruiting of immunosuppressive cells in HCC.•IL-6 expressed by CAFs impaired tumor-infiltrating T cells' function.•IL-6 reversed anti-PD-L1 resistance in HCC mouse model.